Symbolic Form and Real Abstraction: Marxism, Modernism, Iconology - Spaulding, Daniel (The Nordic Journal of Aesthetics, 2025)
This article attempts to sketch the outlines of a materialist theory of artistic symbolization under conditions of generalized commodity exchange, with the aim of advancing a more complex mediation of “form” and “content” in the analysis of artworks. It is here argued that figural processes—in particular, tropes such as prosopopoeia and catachresis—are immanent to capitalist relations because they are implied in the equivalency of unalike things that occurs in the moment of exchange (the phenomenon that Alfred Sohn-Rethel calls real abstraction). The article focuses on three case studies, namely, 1) Immanuel Kant’s account of hypotyposis, or the sensuous symbolization of abstract concepts, 2) the migration of semblance (Schein, in German) from art to economic forms in modernity, as exemplified in the work of modernist painters such as Paul Cézanne and Piet Mondrian, and 3) the suppression of practice in favor of contemplative interpretation in the art historical lineage known as iconology. It is furthermore proposed that it may be possible to write a new history of modernist autonomy in terms of the relation between real abstraction and “automimesis” (the withdrawal of mimetic processes from the representation of external objects to the tautological organization of forms within artworks).